Insect Management for Carrots - Susan E. Webb (EDIS, 2002)
There are no major insect pests on carrot in Florida. The greatest concern for growers has been root damage from soil pests, particularly wireworms (southern potato and tobacco), cutworms (variegated, granulate, black), and mole crickets, all of which are sporadic. Occasional minor pests include leafminers (especially the vegetable leafminer), aphids (green peach and melon), and weevils (especially vegetable weevils). Other arthropods that may occasionally cause minimal damage to carrots in Florida include armyworms (fall, beet, and southern), field crickets, mites (especially twospotted spider mite), and plant bugs (including tarnished plant bug). This document is ENY-462, one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2002. Revised annnually through 2007. Revised March 2010, June 2013, and February 2017. Deaccessioned July 2021.